1999
DOI: 10.1046/j.1440-1622.1999.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficult or Incomplete Flexible Sigmoidoscopy: Implications for a Screening Programme

Abstract: Estimates of the efficacy of flexible sigmoidoscopy as a colorectal cancer screening modality should take into account the relatively high rate of incomplete studies, particularly in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…None the less, this study is, to our knowledge, the first to attempt to quantify the risk of subsequent cancer according to depth of endoscopic insertion. Our results are largely consistent with those of prior studies examining age [5][6][7] and sex [5][6][7][8][9] as risk factors for incomplete sigmoidoscopy. In another recent analysis from the Clinical Outcomes Research Initiative (CORI), Walter et al used data from over 15 000 examinations in asymptomatic persons performed in multiple sites throughout the USA to assess the risk of inadequate sigmoidoscopy (less than 50 cm) by age and sex.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…None the less, this study is, to our knowledge, the first to attempt to quantify the risk of subsequent cancer according to depth of endoscopic insertion. Our results are largely consistent with those of prior studies examining age [5][6][7] and sex [5][6][7][8][9] as risk factors for incomplete sigmoidoscopy. In another recent analysis from the Clinical Outcomes Research Initiative (CORI), Walter et al used data from over 15 000 examinations in asymptomatic persons performed in multiple sites throughout the USA to assess the risk of inadequate sigmoidoscopy (less than 50 cm) by age and sex.…”
Section: Discussionsupporting
confidence: 92%
“…As certain potentially relevant variables were unavailable to us, it remains possible that at least part of the observed association with age and sex is due to uncontrolled confounding. However, other studies that have controlled for the variables above still found associations with age and sex, [5][6][7][8] although admittedly no study has controlled for all of the above variables. Additionally, it is possible that underreporting of examination limitations by clinicians (as discussed above) could lead to residual confounding when this variable is included in the multivariate models, resulting in risk estimates that are too high.…”
Section: Discussionmentioning
confidence: 97%
“…A retrospective study by Brill and Baumgardner,15 which analyzed the factors affecting the depth of insertion of the sigmoidoscope on 223 asymptomatic and symptomatic patients performed by residents at various levels of training, did show a correlation of depth of insertion with female gender, prior abdominal surgery and quality of the preparation. In their prospective study on 206 asymptomatic volunteers, Stewart et al 6 found incomplete depth of insertion in up to a third of the patients and correlated this with female sex, previous abdominal surgery in women, high expectation of pain in women, and poor bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Olynyk et al 5 noted that 30% of patients had a depth of insertion of less than 50 cm. Stewart et al 6 suggest a 25% incomplete examination rate and technical difficulty in up to one third of the cases. Painter et al 7 found that in up to a quarter of the patients, the descending colon was not intubated.…”
mentioning
confidence: 96%
“…The Joint Advisory Group in Endoscopy has defined completion of flexible sigmoidoscopy as insertion of the endoscope to descending colon, and this should be achieved in 90% of examinations. Another study has shown that examination of the entire sigmoid colon was not achieved in 25% of cases, and descending colon was intubated in a minority of cases [6].…”
mentioning
confidence: 99%